2015
DOI: 10.1186/s12884-015-0774-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on preconceptional folic acid supplementation and intention to seek for preconception care among men and women in an urban city: a population-based cross-sectional study

Abstract: BackgroundTo study the knowledge of a large city population on preconception folic acid supplementation and intention to seek for preconception care within an urban perinatal health program.MethodsCross-sectional surveys run in Rotterdam, the Netherlands, in 2007 and annually from 2009 to 2014. A random sample of residents aged between 16 and 85 years was taken each year from the municipal population register. Bivariate analysis, interaction analysis, trend analysis and logistic regression were performed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
7
25
3
Order By: Relevance
“…The finding of this study is in line with studies done in Lebanon [24], the Netherlands [25], China [29], and France [31]. This is probably due to the fact that women who have a high income may have communication media and they may access information regarding folic acid.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of this study is in line with studies done in Lebanon [24], the Netherlands [25], China [29], and France [31]. This is probably due to the fact that women who have a high income may have communication media and they may access information regarding folic acid.…”
Section: Discussionsupporting
confidence: 91%
“…Women who had primary school education, secondary school education, and college and above were 3.9, 4, and 4.8 times more likely had good awareness on preconception folic acid supplementation than women who had no formal education, respectively (AOR 3.94, CI 2.56–4.78; AOR 4.05, CI 2.79–6.94; and AOR 4.77, CI 1.85–6.98). This finding agrees with studies done in Nigeria, Lebanon, the Netherlands, China, and Pakistan [24, 25, 27–29]. The association may be explained by the fact that when individuals are being educated, they can easily read and understand information regarding folic acid and educated women might have interest to read, listen, and watch any information sources.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Williams et al [30] used the United States population-based surveillance system (PRAMS) to measure PCC uptake, which was associated with daily prepregnancy multivitamin consumption and alcohol cessation prior to pregnancy. Several studies have shown that large media campaigns are not always effective in promoting changes in preconceptional lifestyle [31][32][33][34]. Increased awareness and behavioural change both require long-term efforts and are best served by a mix of interventions on the individual and community level delivered over a long period of time [35].…”
Section: Findings In Relation To the Literaturementioning
confidence: 99%
“…Perceptions about preconception care have been assessed in numerous studies. Regarding the “ product,” the general misconception of the need and perceived benefits of preparing for a healthy pregnancy has been acknowledged as the primary challenge to overcome in the delivery of preconception care . The need to address fertility and psychosocial aspects of parenting during PCC is in line with reported low knowledge about fertility (e.g.…”
Section: Discussionmentioning
confidence: 99%